2009
DOI: 10.2298/avb0903243m
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical evaluations of rat soft tissue response to bioceramical implants

Abstract: The purpose of this study was to evaluate the tissue response induced by bioceramical materials (BCM) implanted in rat subcutaneous tissue. Thirty two rats were assigned to 6 groups, as following: control group i.e. not treated; dental ceramic (DC) implants; alfa tricalcium phosphate synthetised at 22 MPa (αTCP22) and at 45 MPa (αTCP45); hydroxyapatite synthetised at 22 MPa (HAP22) and at 45 MPa (HAP45). Contra lateral sides of all test animals represented the blank control surgically incisied at the paraverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The stained slides were selected randomly and captured under magnification 200X using digital image analyzer. The scoring the tissues was conducted according to the methods described by Danica [17] with little modifications for grading of the tissues. The scores for inflammation were defined as: 0 ¼ no inflammation, 1 ¼ mild inflammation, 2 ¼ moderate inflammation and 3 ¼ severe inflammation.…”
Section: Histologymentioning
confidence: 99%
“…The stained slides were selected randomly and captured under magnification 200X using digital image analyzer. The scoring the tissues was conducted according to the methods described by Danica [17] with little modifications for grading of the tissues. The scores for inflammation were defined as: 0 ¼ no inflammation, 1 ¼ mild inflammation, 2 ¼ moderate inflammation and 3 ¼ severe inflammation.…”
Section: Histologymentioning
confidence: 99%
“…Subcutaneous implantation represents a common model for examination of biomaterial characteristics. [35][36][37] After 2 weeks' implantation, the tissue reaction showed a good response to all specimens. Figure 3 shows the histological pictures post subcutaneous implantation.…”
Section: Gross Assessment In In Vivo Studiesmentioning
confidence: 85%
“…This may be a criterion of implant compatibility. 35 The interface qualitatively showed that there were scattered foci of macrophages and foreign body cells surrounding the implant for all groups (score 3). Macrophages were the dominant cell type at the implant surface, playing a major role in cellular responses and tissue reaction.…”
Section: Gross Assessment In In Vivo Studiesmentioning
confidence: 99%
“…In our study, it was reported that the tissue response parameters, tissue damage degree, and duration of tissue recovery around the implant are significantly statistically lower comparing to the tissue inflammatory reaction at the surgical incision site (pseudooperation). 11,13 Macrophages are the basic parameter of these tissue changes, and their number rises in the chronic phases of the wound healing process. 55 Collagenation, encapsulation, and magnification of tissue macrophages are indicators of a receding tissue reaction and its gradual recovery and healing.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluations include the foreign body reaction (FBR), inflammation, encapsulation, and the accumulation of macrophages in the periimplant zone. 11,13,17,18 Evaluation of any new PVA biomaterials for wound dressing requires analysis of the tissue reaction to the implanted material. 5,[19][20][21][22][23] The introduction of silver nanoparticles (AgNPs) into polymer hydrogels increases their antimicrobial activity, 14,[24][25][26][27][28][29] while the incorporation of graphene (Gr) improves mechanical properties.…”
Section: Introductionmentioning
confidence: 99%